2019
DOI: 10.16965/ijar.2018.404
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Characterization of Umbilical Cord Vessels and Neonatal Outcome

Abstract: Morphologic and morphometric characterization of the umbilical cord and vessel components could greatly assist in improving adverse maternal and neonatal outcomes. The aim of this study was to evaluate the relationship between morphometry of umbilical cord vessel components and neonatal outcome. A descriptive cross sectional study was conducted on 207 umbilical cords attached to placentae obtained from Victory Maternity Home and Clinic in Kumasi (Ghana) between November, 2013 and October, 2014. Umbilical cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The present study found that the dominant tissues of the human umbilical cord vessels wall were smooth muscles. A similar finding was observed by Ernst et al [6], in (2013); he found that, the smooth muscles in inner layer runs with the vessel lengthwise, while the outer layer runs in circle ways. Contrary to the findings of Ernst et al [6], in (2013), the present study found that, inner layer runs in circle ways while the outer muscular layer runs with the vessel lengthwise.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The present study found that the dominant tissues of the human umbilical cord vessels wall were smooth muscles. A similar finding was observed by Ernst et al [6], in (2013); he found that, the smooth muscles in inner layer runs with the vessel lengthwise, while the outer layer runs in circle ways. Contrary to the findings of Ernst et al [6], in (2013), the present study found that, inner layer runs in circle ways while the outer muscular layer runs with the vessel lengthwise.…”
Section: Resultssupporting
confidence: 86%
“…A similar finding was observed by Ernst et al [6], in (2013); he found that, the smooth muscles in inner layer runs with the vessel lengthwise, while the outer layer runs in circle ways. Contrary to the findings of Ernst et al [6], in (2013), the present study found that, inner layer runs in circle ways while the outer muscular layer runs with the vessel lengthwise. The arrangement of smooth muscles in wall of cord vessels in this study was found similar to arrangement the smooth muscles in wall of esophagus; this arrangement will allow the cord to shorten and elongate during fetal movements.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…4.5–5.5 mm under physiological pressure) that form a cylindrical helix around the umbilical vein (i.d. 4 mm), while vessels of chorion placenta are highly ramified with a shorter length (1–2 cm) and variable i.d. (0.55–3.2 mm) .…”
Section: Introductionmentioning
confidence: 99%